Критические статьи Андрея Белого 1903–1905 гг. как неомифологические тексты русского символизма - Капинус, Т.Л. (Харківський національний університет імені В.Н. Каразіна, 2011)
В статье исследуется неомифологический аспект критической прозы раннего Андрея Белого. Доказывается, что миф о личности является структурообразующим в критике 1903–1904 гг. Личность в статьях Белого представлена как становление, соответственно сюжетом мифа является преодолеваемый ею внутренний путь. Основные мотивные комплексы критической прозы соотносятся с трехэтапной сюжетной структурой персоналистического мифа. В статье выявляются особенности «неомифологических» символистских текстов, присущие критике Белого: соотношение плана выражения и плана содержания, множественность мифов-шифров, интерпретирующих статьи и т.д. Делается вывод о новом типе критики, возникающем на рубеже веков. The neomythological aspect of the critical prose by early Andrei Bely is researched at the current article. It is proved that the myth of the personality is a structure-formed one in the criticism of 1903–1904. The personality in Bely’s articles is presented as a formation and its internal path forms a plot of the myth. The basic complexes of motifs of the critical prose are correlated with a three-unit structure of the personalistic myth. The features of the neomythological symbolist texts that are inherent in Bely’s criticism are revealed in the article. The critical prose has a special correlation between the mode of expression and the mode of content, the set of myths interpreting the articles, etc. It is concluded that Bely’s critical prose is a new kind of criticism appeared on the turn of the century.
Капінус Тетяна Леонідівна, аспірантка кафедри історії російської літератури Харківського національного університету імені В. Н. Каразіна
Keywords: неомифологизм; критическая проза; миф о личности; мифы-шифры; мотив; символизм